Late arrival of women with pregnancy related complications to Mampong District Hospital-Ghana the underlying factors - Nyarko, Foster (2011)
A thesis submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of MSc.degree in Health Services Planning and Management,